PENGEMBANGAN MEDIA PEMBELAJARAN HYPERLINK BERBASIS CANVA PADA MATA PELAJARAN AKIDAH AKHLAK MATERI ASMAUL HUSNA KELAS X DI MAS MUSLIMAT NU PALANGKA RAYA - Ihsan Auliya Arrasyid; Cindy Elvira; Nur Asyifa Ananda; Abdul Azis (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research aims to develop Canva-based hyperlink learning media for the subject of Asmaul Husna's Aqidah Moral material for class X MAS Muslimat NU Palangka Raya. This development was motivated by the limited learning media used in schools, which only relied on textbooks and simple PowerPoints, causing a lack of motivation and student activity in learning. The research methodology uses a Research and Development (R&D) approach with a 4-D development model (Define, Design, Develop, Disseminate). Data was collected through questionnaires and interviews, involving validation from material and media experts, as well as assessments from subject teachers and student responses. The validation results show a high level of feasibility, with a percentage of 88% from material experts and 80% from media experts. The subject teacher assessment reached 81.67% in the "Very Good" category. The implementation of this learning media produces a positive response from students, which shows increased motivation and involvement in the learning process. Interactive features such as Kahoot quizzes and attractive visual designs have proven effective in creating a more dynamic and enjoyable learning experience. Even though there are technical obstacles such as network problems, overall this learning media has succeeded in overcoming the problems of monotonous delivery of material and the lack of use of technology in learning Aqidah Akhlak. This research contributes to the development of learning methods that are more interactive and appropriate to the digital era, while still maintaining the quality of Islamic religious learning content.